1999
DOI: 10.1046/j.1365-313x.1999.00505.x
|View full text |Cite
|
Sign up to set email alerts
|

AtAMT1 gene expression and NH4+ uptake in roots of Arabidopsis thaliana: evidence for regulation by root glutamine levels

Abstract: SummaryThe mechanisms involved in regulating high-af®nity ammonium (NH 4 + ) uptake and the expression of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
209
2
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(233 citation statements)
references
References 40 publications
20
209
2
2
Order By: Relevance
“…First, the exact nature of the N compounds acting as regulatory signals for the NH 4 + HATS is still unclear. On the one hand, AtAMT1.1 mRNA level is inversely correlated with the concentration of free glutamine in the roots, suggesting a predominant role of this compound as a repressor of AtAMT1.1 expression (Rawat et al 1999). On the other hand, AtAMT1.1 was found to be repressed by short-term NO 3 ¡ supply in a microarray study (Wang et al 2000), indicating that NO 3 ¡ itself could also be involved in AtAMT1.1 down-regulation.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…First, the exact nature of the N compounds acting as regulatory signals for the NH 4 + HATS is still unclear. On the one hand, AtAMT1.1 mRNA level is inversely correlated with the concentration of free glutamine in the roots, suggesting a predominant role of this compound as a repressor of AtAMT1.1 expression (Rawat et al 1999). On the other hand, AtAMT1.1 was found to be repressed by short-term NO 3 ¡ supply in a microarray study (Wang et al 2000), indicating that NO 3 ¡ itself could also be involved in AtAMT1.1 down-regulation.…”
Section: Introductionmentioning
confidence: 97%
“…This regulation is operative in Citrus, where we found a strong correlation between photosynthetic activity in the shoots, NH 4 + HATS activity and CitAMT1 expression, suggesting that the variations in production and transport of photosynthates to the roots are responsible for the diurnal changes of both CitAMT1 expression and NH 4 + HATS activity ). The second regulatory mechanism is the repression exerted by endogenous N assimilates, mediating a negative feedback regulation by the N status of the whole plant (Gazzarrini et al 1999;Rawat et al 1999;Cerezo et al 2001;Loqué and von Wirén 2004). This feedback control modulates both NH 4 + and NO 3 ¡ HATS to match the N demand of the plant, and results in a down-or an up-regulation of the transport systems when the N status is high or low, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using nitrate reductase (NR) mutant plants have shown that nitrate can serve as a metabolic signal for inorganic N that regulates gene expression in Arabidopsis thaliana and other plant species (1)(2)(3)(4). There is also ample though less direct evidence that the assimilated forms of N such as Glu or Gln may also serve as signals that regulate gene expression in plants (5,6). The ability of plants to sense and respond to levels of inorganic and organic N-metabolites provides a mechanism to balance the availability of organic N resources within the plant with the need for N uptake.…”
mentioning
confidence: 99%
“…Couturier et al [24] saw a negative correlation between amounts of transcript of AMT1.2 and glutamine concentration in poplar, which suggests that the expression of ammonium transporters is inhibited by glutamine. Similarly, Rawat et al [25] showed for Arabidopsis that ammonium uptake is strongly correlated with AMT1.2 transcript levels with glutamine functioning as a regulator. Therefore, the presence of glutamine in the spraying solution could have counteracted a potential increase in AMT1.2 transcripts.…”
Section: Effects Of No Fumigation On Gene Expression Of Putative N Trmentioning
confidence: 88%